Leader Ethical Decision-Making in Organizations: Strategies for Sensemaking - Thiel, Chase E.; Bagdasarov, Zhanna; Harkrider, Lauren; Johnson, James F.; Mumford, Michael D. (2012)
Organizational leaders face environmental challenges and pressures that put them under ethical risk. Navigating this ethical risk is demanding given the dynamics of contemporary organizations. Traditional models of ethical decision-making (EDM) are an inadequate framework for understanding how leaders respond to ethical dilemmas under conditions of uncertainty and equivocality. Sensemaking models more accurately illustrate leader EDM and account for individual, social, and environmental constraints. Using the sensemaking approach as a foundation, previous EDM models are revised and extended to comprise a conceptual model of leader EDM. Moreover, the underlying factors in the model are highlighted—constraints and strategies. Four trainable, compensatory strategies (emotion regulation, self-reflection, forecasting, and information integration) are proposed and described that aid leaders in navigating ethical dilemmas in organizations. Empirical examinations demonstrate that tactical application of the strategies may aid leaders in making sense of complex and ambiguous ethical dilemmas and promote ethical behavior. Compensatory tactics such as these should be central to organizational ethics initiatives at the leader level.
Keywords: Sensemaking; Leadership; ethical decision-making; Ethical Behavior; Cognitive strategies